The Comparison of Financial Performance of Sharia Banks Registered in the Jakarta Islamic Index (JII) Using Fundamental Analysis - Arianja, Haidir; Marliyah, Marliyah; Arif, Muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The purpose of this study was to determine the differences in financial performance among Bank Panin Syariah, Bank Syariah Indonesia, Bank BTPN Syariah, and Bank Bukopin Syariah by using fundamental analysis of Earnings Per Share (EPS), Price to Earning Ratio (PER), Return on Equity (ROE), and Debt to Equity Ratio (DER). The research approach is quantitative. Data analysis techniques Normality Test, Homogeneity of Variance Test, Analysis of Variance Test (ANOVA), and Post Hoc Test. The results showed that the calculated F value of earnings per share was 2.437 while the f table value was 2.87, this means that f count f count (7.128) > f table (2.87) so it can be concluded that H0 is accepted which means there is no difference in Earnings Per Share among Bank Panin Syariah, Bank Syariah Indonesia, Bank BTPN Syariah, and Bank Bukopin Syariah. The calculated F value of the Price to Earning Ratio is 8,935 while the f table value is 2.87, this means that f count (34,720) > f table (2.87) so it can be concluded that H0 is rejected, which means that there is a difference in Earnings Per Share among Bank Panin Syariah, Bank Syariah Indonesia, Bank BTPN Syariah, and Bank Bukopin Syariah. The calculated F value of Return on Equity is 3.150 while the value of f table is 2.87, this means that f count (3.150) > f table (2.87) so it can be concluded that H0 is rejected which means that there is a difference in Return on Equity among Bank Panin Syariah, Bank Syariah Indonesia, Bank BTPN Syariah, and Bank Bukopin Syariah. The F calculated Debt to Equity Ratio value is 3,330 while the f table value is 2.87, this means that f count (14,602) > f table (2.87) so it can be concluded that H0 is rejected which means there is a difference in Debt-to-Equity Ratio among Bank Panin Syariah, Bank Syariah Indonesia, Bank BTPN Syariah and Bank Bukopin Syariah.